Respostas
respondido por:
2
vc ponha tudo que tem (x) na frente e o resto atras mudando o sinal pera vou mandar um exemplo
5x + 4 - 2x = 26 - 3x
3x + 4 = 26 - 3x
3x + 3x = 26 - 4
6x = 22
x = 22/6 = 11/3
5x + 4 - 2x = 26 - 3x
3x + 4 = 26 - 3x
3x + 3x = 26 - 4
6x = 22
x = 22/6 = 11/3
thalitagp:
obg
respondido por:
0
5x + 4 - 2x = 26 - 3x
3x + 4 = 26 - 3x
3x + 3x = 26 - 4
6x = 22
x = 22/6 = 11/3
3x + 4 = 26 - 3x
3x + 3x = 26 - 4
6x = 22
x = 22/6 = 11/3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás